AN INIODYMUS DICEPHALIC BUFFALO NEONATE - M. U. Mehmood; W. Abbas; A. Jabbar; J. Khan; A. Riaz; A. Sattar (Journal of Animal and Plant Sciences, 2014)
Dicephalus is a kind of conjoined twins in which two heads share a single body. We here describe a case of six-year-old pregnant buffalo with dystocia due to the dead dicephalic malformed fetus which was presented at Theriogenology Clinic. The dystocia was successfully resolved by fetotomy. The Weight, CRL (Crown Rump Length), Hearth Girth and Height of masculine iniodymus (two skulls with fusion at the occipital region) female fetus were 40 kg, 27 inch, 29.5 inch and 33.5 inch, respectively. The postoperative care was done by administrating ciprofloxicine (Cipoxin, Selmore, Pakistan; 100mg/ml, im) and flunixin meglumine (Loxin®, Selmore, Pakistan; 50mg/ml, im) followed by supportive therapy, calcium borogluconate (Mil-Fone C, Star, Pakistan; each 100 ml contain 26.6 g calcium borogluconate and 5.4 g boric acid, 300ml iv) in combination with amino acids plus vitamins (Amivicom, Star, Pakistan; 0.2-0.5 mg/kg im). In conclusion dystocia, due to dicephalic head could be successfully resolved through fetotomy in field conditions.
Keywords: Iniodymus; Dicephalic; Buffalo; Fetotomy